Análisis del desarrollo de la economía naranja en los emprendimientos juveniles en la zona del Puerto Santa Ana de Guayaquil - Morán Vidal, Gabriela Belén (2020)
The orange economy is an economic model that offers development opportunities to those who apply it, this concept is associated with three criteria: innovation, creativity and cultural heritage. Globally, the orange economy represents a significant contribution to PIB, having a strong presence in countries such as the United States and China. Regarding Latin America, the orange economy has been growing gradually, where Ecuador is one of the countries in the region with a high rate of early entrepreneurship, which how the potential that exists in the country for the optimal development of this economic model………..